Behavior of Stimulus Response Signals in a Rat Cortical Neuronal Network Under Xe Pressure. (1st August 2022) - Uchida, T.; Kubota, T.; Tanabe, R.; Yamazaki, K.; Gohara, K.
Graphical abstract: Highlights: The stimulus response via synaptic connections is suppressed at Xe pressures above 0.3 MPa. Xe induced suppression of the response rate is less sensitive than that of the synchronous burst. Hill-equation fitting to the Xe pressure dependence of the stimulus response rate shows multiple suppression points. The signal transduction on the axons is also depressed, only in response rate at Xe pressures above 0.3 MPa. Abstract: Neurons cultured on a multi-electrode array show not only spontaneous firing, but also network-specific burst firing, the latter of which develops into synchronous bursting. Such synchronous bursting can be suppressed by exposure to xenon (Xe) gas. To better understand such suppression of bursting by Xe, we investigate here whether signal transmission between neurons is also suppressed under these conditions. In these experiments, we apply a pulse electrical-stimulus to one electrode and observe the response signals within 10 ms at other active electrodes. When put under a sufficient Xe pressure, some response signals become delayed or vanish after disappearance of synchronous-bursts, particularly signals passing through multiple synaptic bonds. Such bonds have a high probability of having delayed or vanishing signals when the Xe pressure is above 0.3 MPa. The pressure dependence of the response ratio to the stimulus suggests that Xe suppresses multiple points of action simultaneously when suppressing synaptic signal transduction, as observed in the suppression of the synchronized bursting. In addition, we find that the signal that transmits not via synaptic bonding (axon conduction) is also suppressed under Xe gas pressures over 0.3 MPa. Therefore, we conclude that Xe-induced suppression of synchronized bursting is caused mainly by a decrease in the apparent number of active neurons that contribute to the neuronal network, a decrease due to inhibition of signal transmission via synaptic connections.